In Vitro Study of Garcinia dulcis (Roxb.) Kurz Leaves Extract against Hepatitis C Virus: Garcinia dulcis Leaves Extract against Hepatitis C Virus - Apriyanto, Dadan Ramadhan; Hartati, Sri; Sri Wahyuni, Tutik; Inge Lusida, Maria (Journal of Tropical Life Science, 2024)
Garcinia dulcis is a plant commonly used in traditional medicine in tropical regions. It has anti-bacterial, anti-inflammatory, anti-tumor, and anti-malaria properties. Despite its potential benefits, studies on its effectiveness as an antiviral are limited. This study investigated the antiviral properties of G. dulcis leaf extract against the JFH-1 strain genotype 2a as a treatment for Hepatitis C Virus (HCV). Huh7it-1 cells infected with the HCV genotype 2a strain JFH-1 were used to determine the antiviral effect of methanol extracts of G. dulcis leaves (GD-LE). GD-LE antiviral activity was investigated using a focus-forming assay for anti-HCV and 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay for cytotoxicity. A time-of-addition study of anti-HCV was also performed to determine the mode of action of GD-LE. The results showed that GD-LE inhibited HCV replication with an IC50 of 17.06 µg/mL without giving any toxicity to the cells. The mode-of-action of GD-LE was found to inhibit HCV replication in the co-addition and post-infection stages. These findings suggest that GD-LE could be a promising candidate for anti-HCV treatment. However, further study regarding GD-LE bioactive compound isolation needs to be done to prepare an effective antiviral.